Respuesta :
Answer:
Option 3
Step-by-step explanation:
We need to find a pair which shows equivalent expressions.
First equation is
[tex]2x+10=-2(x-5)[/tex]
[tex]LHS=2x+10[/tex]
[tex]RHS=-2(x-5)=-2(x)-2(-5)=-2x+10[/tex]
[tex]LHS\neq RHS[/tex]
Option 1 is incorrect.
Second equation is
[tex]-2(x+5)=2x-10[/tex]
[tex]LHS=-2(x+5)=-2(x)-2(5)=-2x-10[/tex]
[tex]RHS=2x-10[/tex]
[tex]LHS\neq RHS[/tex]
Option 2 is incorrect.
Third equation is
[tex]-2x-10=-2(x+5)[/tex]
[tex]LHS=-2x-10[/tex]
[tex]RHS=-2(x+5)=-2(x)-2(5)=-2x-10[/tex]
[tex]LHS=RHS[/tex]
Option 3 is correct.
Fourth equation is
[tex]-2(x–5)=-2X-10[/tex]
[tex]LHS=-2(x–5)=-2(x)-2(-5)=-2x+10[/tex]
[tex]RHS=-2x-10[/tex]
[tex]LHS\neq RHS[/tex]
Option 4 is incorrect.
Therefore, the correct option is 3.